A simple model of the commercial lobbying industry - Thomas Groll; Christopher J. Ellis (Center for Economic Studies and ifo Institute (CESifo), 2013)
In this paper we model the commercial lobbying industry (such as the so-called K-Street lobbyists of Washington, D.C.). In contrast to classical special interest groups commercial lobbying firms are not directly motivated by policy outcomes. They exist to make profits by selling intermediaries services between their clients and policymakers. We explain why these firms exist, and their implications for social welfare. We find that in a simple general equilibrium framework the market level of commercial lobbying services is typically socially inefficient, and characterize the nature of the distortions involved.
Keywords: D72; D82; 330; lobbying; influence activities; information acquisition; financial contributions; commercial lobbying firms; political access